A study of the stressors and coping behaviors of parents of Chinese hemophilic children. (June 2017) - Peng, Jie; Yang, Hongbin; Fu, Gan; Zhao, Xielan; Li, Xiaolin; Chen, Fangping
To understand the stressors experienced by parents of hemophiliac children in China and the coping behaviors utilized, semi-structured interviews were conducted with parents of 158 Chinese hemophiliac children. We administered the Coping Health Inventory for Parents to determine coping behaviors. Parents' main stressors were in the domains of children's illness and physical condition, economic problems, and so on. Parents engaged in various positive coping behaviors to manage these stressors. The helpfulness of these coping behaviors in maintaining a normal family life differed significantly by parents' education and income ( p < .01). Parents of hemophilic children in China face numerous stressors but engage in a number of coping behaviors to manage these stressors. While treating hemophilic children, Chinese medical workers should guide parents to adopt such positive coping behaviors.